The antipsychotic amisulpride: ultrastructural evidence of its secretory activity in salivary glands. (10th December 2013) - Loy, F; Isola, M; Isola, R; Lilliu, MA; Solinas, P; Conti, G; Godoy, T; Riva, A; Ekström, J
<x xml:space="preserve">Abstract</x> Objective Amisulpride is reported to inhibit clozapine‐induced sialorrhea. Preclinically, clozapine evokes muscarinic‐M1‐type‐mediated secretion that, however, amisulpride does not reduce. Instead, amisulpride, without causing any overt secretion per se, enhances both nerve‐ and autonomimetic‐evoked salivation by unknown mechanism(s). Hypothesizing that amisulpride prepares the gland for secretion, we looked for ultrastructural events indicating secretory activity in intercellular canaliculi of serous/seromucous cells, that is, density increase in protrusions (reflecting anchored granules) and in microbuds (reflecting recycling membranes and/or vesicle secretion) and decrease in microvilli (reflecting the cytoskeletal re‐arrangement related to exocytosis). Material and Methods Rat parotid and submandibular glands were exposed to amisulpride in vivo or in vitro. Glands were processed for transmission electron and scanning electron microscopy and then morphometrically assessed. Results Cells were packed with secretory granules. The density of protrusions increased in both glands, whereas significant and parallel changes in microvilli and microbuds occurred only in parotid glands, and in vitro. Conclusions Amisulpride induced ultrastructural signs of secretory activity but to varying extent; in submandibular glands, in contrast to parotid glands, changes were not brought beyond the granular anchoring stage. Amisulpride may provide an overall readiness for secretion that will result in augmented responses to agonists, a phenomenon of potential interest in dry‐mouth treatment.